Who Talks to Whom? An Analysis of Information Flows in Malawi’s Agricultural Research Network - Yauney, Jason; Thangata, Paul Howard; Droppelmann, Klaus; Mapila, Mariam A.T.J. (International Food Policy Research Institute, 2012)
A Social Network Analysis (SNA) of agricultural research institutions in Malawi was performed to investigate networking and knowledge sharing in relation to the implementation of the Agricultural Sector Wide Approach (ASWAp). SNA helps explain how the different actors relate to one another, and how these relationships affect the generation, exchange, and use of information and knowledge in ASWAp implementation. The ASWAp is Malawi’s Comprehensive Africa Agriculture Development Program (CAADP) compact. It articulates Malawi’s ambition to transform and diversify its agricultural sector with the aims of raising agricultural productivity, improving food and nutrition security, and increasing the incomes of rural people. Agricultural research plays a vital role in making the programme a success.